A Personal View from the Precipice - Perkins, Elizabeth (LiNQ (Literature in North Queensland), 2016)
Elizabeth Perkins reviews: Joan Priest, The Literary Precipice. Scribblers Publishing. 148 pp. $19.95 (plus $5.00 postage) from Scribblers Publishing, P0 BOX 501, MUDGEEREBA, QUEENSLAND 4213. ISBN 0-9586737-3-3.